Die deutschen Herrscher des Mittelalters: historische Portraits von Heinrich I. bis Maximilian I. (919 - 1519) - Schneidmüller, Bernd; Weinfurter, Stefan (Beck, 2003)
Das Mittelalter im Spiegel seiner Herrscher